Bridging the gap (combining on-the-field-experiences and new technologies in training) - Oldham, M. (Techniques Magazine, 2024)
We have watched the American flag rising and heard the national anthem playing during the medal ceremonies in every Olympics in modern history. National pride soars and athletes, and their coaches, are applauded for the ultumate prize. USA Track and Field (USATF) has been a dominant force in that medal hunt over the last 50 years, both on the men´s and women´s side, for numbers of medals awarded, world records, and overall dominance with over 1,900 athletes competing since 1896 and 865 medals won (Landry, 1987; Mallon and Mason, 2013) Yet, of the 24 Olympics, where USA entered a decathlon athlete, only 27 medals have been won, and since 1984 only four USA heptathlon athletes have medaled. How then can USATF elevate itself to be as dominant in heptathlon and decathlon as it is in many of the other track and field events? Our belief is that sport science data play a major role in how athletes prepare for each event within the mulit-event day competition. Coaches have long since used a variety of "coaching triangles," (e.g., practice, compete, evaluate) to structure how they evaluate athletes and structure best practices for training (Payne & Hagge, 2010). Yet few common practices, with definitive results or correlations, have been established for the heptathlon and decathlon. This article aims to provide some insight as to how to apporach the gap between data that can be acquired by "old-school" field tests and "new-age" technology, how those two areas can be complimentary and how to apply this data knowledge to the daily training of heptathletes and decathletes.